Targeting the P2Y13 Receptor Suppresses IL-33 and HMGB1 Release and Ameliorates Experimental Asthma - Werder, Rhiannon B; Ullah, Ashik; Rahman, Muhammed Mahfuzur; Simpson, Jennifer; Lynch, Jason P; Collinson, Natasha; Rittchen, Sonja; Rashid, Ridwan B; Sikder, Al Amin; Handoko, Herlina Y; Curren, Bodie F; Sebina, Ismail; et al. (American journal of respiratory and critical care medicine, 2022)
Werder et al discuss their study which aims to determine whether P2Y13-R (P2Y13 receptor), a purinergic GPCR (G protein-coupled receptor) and risk allele for asthma, regulates the release of IL-33 and HMGB1 (high mobility group box 1). The role of P2Y13-R in AEC function and in the onset, progression, and exacerbation of experimental asthma was assessed by using pharmacological antagonists and mice with P2Y13-R gene deletion. They identify P2Y13-R as a novel gatekeeper of the nuclear alarmins IL-33 and HMGB1 and demonstrate that the targeting of this GPCR via genetic deletion or treatment with a small-molecule antagonist protects against the onset and exacerbations of experimental asthma.